The tentacles of imperialism on Latin America: Nicaragua and magical realism in favor of the interests of the North - Segura Umaña, Gabriela (2021)
In this article a review is carried out on a series of historical events that occurred in Nicaragua between 1920 and 1933, which were reflected in several deliveries of Repertorio Americano. In the review, it becomes imperative to shape one of the actors so present in the reality of this Central American country, one who has used the collusion between magical events and chameleonic beings that have served its interests. With the help of Julio Cortázar’s intertext, this essay gives an account of the current affairs of the United States’ tricks and all its imperialist machinery.